1996
DOI: 10.1111/j.1432-1033.1996.0807h.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and Characterization of a Thyroid Ca2+‐Dependent and NADPH‐Dependent K3Fe(CN)6 Reductase

Abstract: The thyroid plasma membrane contains a Ca"-regulated NADPH-dependent H,O,-generating system which provides H,O, for the thyroid-peroxidase-catalyzed biosynthesis of thyroid hormones. The molecular nature of the membrane-associated electron transport chain that generates H,O, in the thyroid is unknown, but recent observations indicate that a flavoprotein containing a FAD prosthetic group is involved. Solubilization was reinvestigated using 3-[(3-cholamidopropyl)dimethylammonio]-l -propanesulfonate (Chaps), Trit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…These data are in good agreement with those of Raspé and Dumont (10), who reported that TSH induces H 2 O 2 generator activity in dog thyrocytes by activating the adenylate cyclase cascade. They also corroborate our results showing that the TSH and/or forskolin stimulate NADPH oxidase activity in pig thyrocytes (11), which seems to be correlated with a higher expression of the flavoprotein (16).…”
Section: Tissue Distribution Of the P138supporting
confidence: 81%
See 2 more Smart Citations
“…These data are in good agreement with those of Raspé and Dumont (10), who reported that TSH induces H 2 O 2 generator activity in dog thyrocytes by activating the adenylate cyclase cascade. They also corroborate our results showing that the TSH and/or forskolin stimulate NADPH oxidase activity in pig thyrocytes (11), which seems to be correlated with a higher expression of the flavoprotein (16).…”
Section: Tissue Distribution Of the P138supporting
confidence: 81%
“…However, the partially purified flavoprotein is still able to catalyze the NADPH-dependent reduction of the electron scavengers nitroblue tetrazolium and potassium ferricyanide (K 3 Fe(CN) 6 ). We used this property to detect and quantify the flavoprotein activity during its purification (16). We have now purified the thyroid oxidase flavoprotein as a first step in defining the molecular structure of the enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these convincing arguments, the definite proof that ThOX1 and ThOX2 are components of the thyroid H 2 O 2 generating system will await reconstitution of H 2 O 2 production in transfected nonthyroid cells. This may require co-transfection of constructs encoding additional components that remain to be identified (10).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is formed from the oxidation of NADPH by an NADPH oxidase, a flavoprotein that has been partially purified from solubilized pig thyroid plasma membrane (10). It is known that the enzyme requires Ca 2ϩ to be fully active, but the precise molecular structure of the H 2 O 2 generating system operating in the thyroid remains ill defined.…”
mentioning
confidence: 99%